Formation of Î¼-Carbonulmethulidene Moiety from Î¼3-Methylidyne Moiety on the Triosmium Cluster Framework (Journal of Bangladesh Academy of Sciences, 2009)
doi: 10.3329/jbas.v32i2.2435 Journal of Bangladesh Academy of Sciences Vol.32(2) 2008 160-162